Dance with me eaudiobook - Rice, Luanne (Recorded Books Inc., 2004)
New York Times best-selling author Luanne Rice magnificently captures the sentiments that homecomings evoke. Romantic Times raves "Rice's honest, salt-of-the-earth characters quickly bring the reader into their lives and hearts." A prodigal daughter returns to her small-town home to take care of her ailing mother and to search for the child she gave up for adoption years ago.